1998
DOI: 10.3109/08860229809045090
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Glomerular Filtration Rate and Renal Plasma Flow in Cirrhotic Rats During Converting Enzyme Inhibition

Abstract: During the development of cirrhosis ascites-edema, peripheral vasodilatation, hypotension and an increase of the plasma concentration of several neurohormones are frequently observed. Such complex changes in the hormonal profile hinders the assessment of the relative role of each in the pathophysiology of this disease. The purpose of this work was to evaluate in a rat model of experimental cirrhosis (phenobarbital/CCl4) the role of the renin-angiotensin system in the pre-ascitic stage of the disease using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The untreated CBDL rats of the present study were markedly hypotensive. In fact, they tended to be more hypotensive than in several previous studies [32,[37][38][39][40]. However, this degree of hypotension is not a unique finding [41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The untreated CBDL rats of the present study were markedly hypotensive. In fact, they tended to be more hypotensive than in several previous studies [32,[37][38][39][40]. However, this degree of hypotension is not a unique finding [41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 55%
“…In addition, increased local quenching of NO by superoxide (suggested by the high intrarenal levels of F 2 -isoprostanes) may leave the kidney susceptible to the unopposed effects of these vasoconstrictors. The increase in intrarenal angiotensin II and ET may explain why angiotensinconverting enzyme inhibitors (ACEI) [40], or ET antagonists [69] improve renal hemodynamics in cirrhotic rats. However, the use of these agents is severely limited because blood pressure tends to fall precipitously.…”
Section: Discussionmentioning
confidence: 99%
“…Further assessment of the IV kinetic parameters indicated that the forward rate constant from the central to the tubular compartment (K 13 ) was an extremely rapid process. This is unsurprising when one considers that this rate constant essentially represented elimination from the central compartment via glomerular filtration, which is expected to be a rapid process (i.e., ≈20−30% renal plasma flow rate 23 ). The model parameters governing saturable reabsorption further supported the assertion that the tubular compartment mechanistically represented the proximal tubule and kinetically identical spaces.…”
Section: ■ Discussionmentioning
confidence: 99%
“…and surgically prepared for a renal clearance experiment as described previously (Ibarra et al. ). The trachea was cannulated to facilitate breathing.…”
Section: Methodsmentioning
confidence: 99%